Assessment of prescription pattern using WHO drug prescribing indicators in medicine wards of a tertiary care teaching hospital: a retrospective observational study - Bachewar, Narendra P.; Choudhari, Sachin R.; Dudhgaonkar, Sujata (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Rational prescribing is an essential skill for every prescriber. However many times it seems a difficult task for various reasons. Such practices ultimately increase the mortality, morbidity and financial burden on the patient. Hence, we aimed our study to evaluate appropriateness of prescription pattern according to WHO drug prescribing indicators, few complementary indicators and classify prescription errors. Methods: A retrospective observational study, conducted in medical record section of tertiary care teaching hospital of Maharashtra during the period of 6 months. Total 400 randomly selected prescriptions from Medicine inpatient wards were scrutinized. Results: Average number of drugs per prescription was 5.20 trending towards polypharmacy. Drugs prescribed by generic name were 13.88%, injectable drugs were part of 93.50% prescriptions, 78.25% prescriptions contained an antimicrobial agent and Percentage of drugs prescribed from NELM 2011 was 72.36%. Illegible handwriting in 68% cases was the important cause of prescription errors. These errors found in 73% of prescriptions. Conclusions: The present study showed that the practices were trending towards irrational prescribing. Polypharmacy and illegible prescriptions were dominated. Regular prescription audit will help to rectify such practices. Also, there is an urgent need of sensitization of prescriber through new treatment guidelines, seminar, presentations and discussions on regular basis.